Influence of Credit Risk Management and Specific Bank Factors on Financial Performance in Publicly Listed Banks - Alda Emilia Suryanto; Imronudin Imronudin (Borong Newinera Publisher, 2024)
This research is motivated by financial problems which are a period of conflict in the banking or financial sector. Among all the world's continents, Asia is the most crucial continent and contributes 60% of world growth but faces the problem of high non-performing loans (NPL). As is known, a high NPL ratio will weaken the country's economy or financial position. Therefore, the research was conducted in Indonesia. Two credit risk systems are used in this research: NPL and capital adequacy ratio (CAR). Apart from that, this research also includes bank-specific factors to improve financial performance. This research analyzes the relationship between credit risk, bank-specific factors, and FP. The data analysis method used in this research is a quantitative data analysis method, this research is panel data regression using Eviews software. Research results related to NPL (Non-Performing Loans) have no effect on financial performance, Research related to the capital adequacy ratio (CAR) which has no effect on financial performance, Research shows that the cost efficiency ratio (CER) has no effect on financial performance, Research shows that interest rates average loan interest (ALR) has an effect on financial performance, and research shows that the liquidity ratio (LR) has a significant effect on financial performance. The results of this research can help to improve financial performance by paying attention to credit risk management, taking appropriate techniques efficiently in providing loans and looking at liquidity position as a factor.